Development of processing technology and mathematical model of modification of magnesite raw material - LESKO, MICHAL; BAKALÁR, TOMÁS (Boletim Paranaense de Geociências, 2002)
The application of physical and physical-chemical methods of magnesite processing related to the physical, chemical and mineralogical properties of particular magnesite types are presented in this paper. The best product qualities, achieved depending on the degree of liberalization of components contained in the magnesite, are shown. Possibilities and advantages of modelling of mineral processing methods applied to magnesite are also exemplified.